2005
DOI: 10.1002/ijc.21263
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of p53 genotypes and haplotypes in tobacco‐associated leukoplakia and oral cancer patients from eastern india

Abstract: The role of 3 p53 polymorphisms (16 bp duplication at intron 3, codon 72 Arg/Pro and intron 6 NciI RFLP at np 13494) as potential markers for indicating cancer risk remains inconclusive. In our case-control study consisting of 197 leukoplakia and 310 oral squamous cell carcinoma (SCC) patients and 348 controls, genotype frequencies at these 3 p53 loci were determined by PCR-RFLP method and analyzed by multiple logistic regression to determine the risks of the diseases. The 2/2 genotype at codon 72 of p53 was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 50 publications
4
34
5
Order By: Relevance
“…Odds ratios (ORs) and 95% Confidence Intervals (CIs) were calculated for the risk estimation of oral cancer development. The highest proportion of a homozygous genotype at any particular p53 locus in the control group was considered as referent genotype to estimate risk associated with these polymorphisms (Mitra et al, 2005). Linkage disequilibrium analysis was performed for the study groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Odds ratios (ORs) and 95% Confidence Intervals (CIs) were calculated for the risk estimation of oral cancer development. The highest proportion of a homozygous genotype at any particular p53 locus in the control group was considered as referent genotype to estimate risk associated with these polymorphisms (Mitra et al, 2005). Linkage disequilibrium analysis was performed for the study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, most of reports are on Arg72Pro polymorphism of p53 gene. There is only one study from eastern region of India, explored the role of these three polymorphisms in oral cancer (Mitra et al, 2005). They have observed that the Proline allele was more frequent in control population and no association was found between oral cancer risk and Arg72Pro polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations